MITOLOGI NUNDUNG BHUTA KALA PADA RANGKAIAN HARI SUCI NYEPI SEBAGAI WUJUD PENGKONDISIAN ETIKA UMAT HINDU DI BALI - Oka Sugiharta, I Putu Suweka; Yogantara, I Wayan Lali (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
This research aims to describe and analyze the Nundung Bhuta Kala Mythology during the Nyepi Holy Days as a form of ethical conditioning for Hindus in Bali. This research is a qualitative descriptive type because it focuses on analyzing non-numerical data. The data for this research comes from the stories of Hindus in Bali regarding the mythology of nundung bhuta kala during the holy day of Nyepi. Data analysis in the research was carried out by following Miles and Huberman's stages; data collection was followed by reduction, presentation, and verification/drawing conclusions. The results of this research reveal that there is an element of ethical conditioning of Hindus in Bali in the Nundung Bhuta Kala Mythology, a series of Nyepi Holy Days. Nundung Bhuta is interpreted as steadfastness against external temptations and avoidance of bad habits. There are three variants of ethical conditioning that occur, such as individual ethics, social ethics, and ecological ethics. Individual ethics is an internal and autonomous aspect of every human being. Sociological ethics displays the way humans relate harmoniously to other people. Ecological ethics shows efforts to preserve the natural environment, which is a place for humans to shelter. Keywords: Nundung Bhuta Kala Mythology, Nyepi, Ethical Conditioning, Balinese Hinduism